Asian popular culture - Fung, Anthony Y. H. (Media, culture, and social change in Asia series ;, 2013)
"Examines two seemingly contradictory and yet parallel processes in the circulation of Asian popular culture: the interconnectedness between Asian popular culture and western culture in an era of cultural globalization, and the local derivatives and versions of global culture that are necessarily disconnected from their origins in order to cater for the local market"--Provided by publisher.